Agricultural policy in disarray: Reforming the farm bill—An overview - Smith, Vincent H.; Glauber, Joseph W.; Goodwin, Barry K.; Sumner, Daniel A. (American Enterprise Institute, 2017)
In general, farm programs authorized by the 2014 Farm Bill channel federal funds to households whose incomes and wealth are well above those of the average US household. Many of those programs also create incentives for farm businesses to operate in ways that waste economic resources, and the owners and managers of those businesses respond accordingly. For example, the federal crop insurance program creates incentives for moral hazard behaviors that expand crop production on highly erodible land and affect the allocation of land between alternative crops. The US sugar program encourages beet and cane operations to expand production in ways that waste resources and increase the prices consumers pay for many food products. These and other programs—such as the price and income support initiatives introduced in the 2014 Farm Bill for major crops such as corn, soybeans, wheat, peanuts, and rice—also hurt world prices, creating challenges for the United States in its trade relations with other countries. Two of these programs, Price Loss Coverage and Agricultural Risk Coverage, cost US taxpayers more than $8 billion in fiscal year 2017. Marketing orders for other commodities—including milk, fruits, and some vegetables—also distort production incentives, wasting land, labor, water, and other scarce resources. In addition, many conservation programs that pay farmers to adopt or continue conservation practices are poorly targeted and add little to the quality of the environment but in total cost taxpayers more than $5 billion a year. As Congress considers a new farm bill, members should seriously pay attention to proposals that terminate farm subsidy, marketing order, trade, and conservation programs, which waste scarce economic resources, raise food prices, and channel taxpayer monies to wealthy farmers, with few benefits for consumers or the environment, and which make no observable contributions to alleviating rural poverty.